Degeneração corticobasal: aspectos neuropsiquiátricos, neuropatológicos e de neuroimagem em 70 pacientes - Caixeta, Victor de Melo (2015)
Background: Corticobasal Degeneration (CBD) is an rare and heterogeneous disease in its presentations, representing an great diagnostic challenge. There aren´t, in Brasil, large CBD case series, and there aren´t many in the world as well. Its cognitive and behavioural aspects have received little (despite growing) attention. Objectives: To describe sociodemographic, clinic, neuropsychiatric, neuropathological, and neuroradiologic aspects in a large brazilian DCB case series. To perform a literature review on CBD, with special focus on cognitive and behavioural aspects. Methods: 70 patients data was collected, with CBD diagnosis according to the Cambridge criteria modified by Bak and Hodges (2011). The patients underwent clinical, neuropsychiatric, neuroradiologic (structural and functional) and pathologic (in six cases) retrospective analysis. There were studied clinical, sociodemographic, neuropsychiatric, neuroanatomic variables and family history. Results and Discussion: The mean age at onset was 62.8 years (sd=9,5), and both sexes were equally affected (52,9% male). Hemispheric asymmetry was present in 97% of cases, and the left brain hemisphere was the most affected (68,2% of cases). The most frequent initial presentation was “psychiatric” (with changes in behaviour and/or mood), present in 68,1% of cases, followed by motor-extrapyramidal presentation (54.3%). In the course of the disease, the predominant clinical form (phenotype) was the extrapyramidal-motor with 61.4% of cases, followed by "psychiatric" with 51.4%. There were five cases with presentation of Posterior Cortical Atrophy (PCA) In 37.7% there were not found classic CBD syndromes (e.g., alien hand syndrome). We found 18.7% of cases with family DCB, with four families presenting a phenotype not yet described, of CBD with NPH (Normal Pressure Hydrocephalus). We also observed cognitive and functional impairments in the evaluated scales (MMSE, Pfeffer and CDR), and frequent medical and psychiatric comorbidities, especially diabetes mellitus (23.5%), hypothyroidism (22.1%) and Bipolar Spectrum Disorders (46, 4%), the last two significantly more frequent in the sample. There were six cases of rapidly progressive DCB and six confirmed by autopsy CBD cases in the sample. Conclusion: We observed, in agreement with the literature, a wide variety of CBD presentations, including new and little described phenotypes (NPH and PCA). In the characterization of the sample, we observed a great prevalence and importance of cognitive, affective and behavioural presentations.